RANCANG BANGUN PROTOTIPE MANOMETER GAS DIGITAL YANG TERKALIBRASI OLEH STANDAR PRIMER PRESSURE BALANCE - Prakosa, Jalu Ahmad (Instrumentasi, 2013)
To meet market needs and become independent for technology, Domestic and calibrated of digital manometer products is urgent. The purpose of this study is to create a prototype of digital gas manometer that calibrated to guarantee the truth measurement in international. The designing and creating of digital manometer that traceable to gas pressure calibration system, pressure balance has been done at pressure laboratory of Puslit KIM LIPI. ATmega328 microcontroller on the Arduino Uno board is used to acquire the output voltage data of pressure sensor MPX5500DP by using 10 bit Analog to Digital Converter (ADC) and communicates serially via the PC with USB port also displays the measurement results in real time with Liquid Crystal Display (LCD). From the results of calibration and measurement in the measuring range of 50-370 kPa obtained that the average maximum absolute error of reading is 0.198% while the largest maksimum absolute errors contained in the measuring point of 50 kPa is 1.003% and the smallest maximum absolute error contained in the measuring point of 330 kPa is 0.058%. The ratio of the economic benefits of this digital gas manometer is approximately to four point three than similar products made overseas that has been on the market so it is worth to be further developed to the stage of incubation. Key words: digital manometer, calibration, Arduino Uno, pressure balance